Effectiveness of accrual basis accounting system in state budget and treasury system in TAM 3 framework - Ratih Kusumastuti; Derist Touriano; Sry Rosita; Raja Sharah Fatricia (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Purpose - This study establishes a basic theoretical model developed using Technology Acceptance Model (TAM 3) with several critical factors on the effectiveness of accrual basis accounting systems in the State Budget and the Treasury System.Method - This basic research uses a causal model with primary data collected quantitatively and presented descriptively. The study population was users of the State Budget and Treasury System in the Regional Office V of Jambi Province using the convenience sampling method.Result - The results of this study stated that all TAM variables were correlated with each other and TAM 3 variables were correlated with the effectiveness of the accrual-based accounting system in SPAN. It was proven that there was a significant relationship between all variables. However, the accrual-based accounting system in SPAN practically does not provide convenience and tends to have low intensity of use and low effectiveness.Implication - The result of this research states that all variables of TAM are correlated to each other and TAM 3 variables are correlated to the effectiveness of accrual basis accounting system in SPAN.Originality - This study focuses on the effectiveness of accrual basis accounting system in State Budget and Treasury System: migration of the Indonesian Islamic banking system of BSI.